In vitro antioxidant, antimicrobial and cytotoxic activities and green biosynthesis of silver & gold nanoparticles using Callistemon citrinus leaf extract - Amal M. Saad, Abdel-Aleem H. Abdel-Aleem, Mosad A. Ghareeb, Manal M. Hamed, Mohamed S. Abdel-Aziz, Asmaa H. Hadad (Journal of Applied Pharmaceutical Science, 2017)
The current study was aimed to synthesis and characterization of silver (AgNPs) & gold (AuNPs) nanoparticles using Callistemon citrinus leaf extract, and to evaluate their in vitro antioxidant, antimicrobial and cytotoxic activities as well as their total phenolic content (TPC). Silver and gold nanoparticles were synthesized and characterized via UV-vis absorbance spectroscopy, transmission electron microscopy (TEM), and X-ray diffraction (XRD) analyses. The antioxidant activity was evaluated using dot-blot and DPPH staining, and via phosphomolybdenum assays. Also, the in vitro antimicrobial activity was evaluated via disc agar plate method. The cytotoxic activity was evaluated via brine shrimp lethality test (BSLT), and TPC was estimated via Folin-Ciocalteu’s assay. The transmission electron microscopy (TEM) analysis showed that the sizes of the synthesized AgNps were ranged from 8 to 14 nm with maximum UV/vis absorbance at 450nm. Also, the synthesized AuNPs exhibited an average size of 5.8 to 8.84 nm with maximum UV/vis absorbance at 535nm. Moreover, the results revealed that TPC of the tested extracts was ranged from 548.85 to 123.30 mg gallic acid equivalent (GAE)/g dry extract. The total antioxidant capacity (TAC) was ranged from 643.90 to 147.96 mg ascorbic acid equivalent/g dry extract. Furthermore, there is a promising antimicrobial activity against four strains with inhibition zones were ranged from 8.5 to 15.5 mm, Penicillin G was used as positive control at concentration of 100 μg/disc. In terms of LC50 the n-butanol extract (63.09 μg/ml) was the most potent cytotoxic, followed by EtOAc (100.0 μg/ml). In, conclusion the leaves of Callistemon citrinus showed a noticeable antioxidant, antimicrobial & cytotoxic activities and the ability to produce AgNPs and AuNPs.
Keywords: Callistemon citrinus, antioxidant, antimicrobial, cytotoxic, TPC, AgNPs, AuNPs, UV-vis, TEM, XRD.